Paediatric nurses' attitudes towards the promotion of healthy eating - Blake, Holly; Patterson, Joanna (Mark Allen Healthcare, 2015)
This study assessed paediatric nurses' attitudes towards promoting healthy eating and their opinions regarding nurses as role models for health. In all, 67 nurses from 14 wards at an acute hospital trust completed questionnaires on weight, diet, physical activity, self-efficacy and attitudes towards nurses as role models for health. Forty-eight percent felt that they could incorporate health promotion into their patient care better, and 84% believed that nurses should present themselves as role models for health. Nurses felt that their own health behaviours influenced the quality of their care: 77% reported that patients and families would heed advice better from those who appeared to follow it themselves, and 48% reported difficulties in promoting health behaviours they did not adhere to themselves. These views were inconsistent with their own lifestyle choices, since one third of respondents did not meet physical-activity guidelines, almost half were an unhealthy weight, and the majority did not consume five portions of fruits/vegetables per day. Paediatric nurses identified barriers and facilitators to promoting healthy eating. Education, training and access to evidence-based resources may help to increase paediatric nurses' confidence to promote healthy eating to children and their families. Hospital workplaces should make provision to support nurses who seek to improve their own health.